Televising the Red Captain: Aleksandr Zuzenko as shown to Soviet viewers. Issue 1 (3rd April 2017) - Windle, Kevin
ABSTRACT: The revolutionary sailor, journalist, and Comintern agent Aleksandr Zuzenko achieved renown for his role in leading strikes and demonstrations in Australia, whence he was deported in 1919 and again in 1922. He became known to readers of Soviet literature in the 1920s and 1930s, but literary celebrations of his life came to an end with his execution in 1938 as a "British spy". Thirty years later, after his rehabilitation, he experienced a posthumous revival not only in literature but also on television and radio, in feature programs made with the assistance of his surviving family and old shipmates. This article considers the scripts for a 1967 television feature, Chelovek iz legendy ( A Man from a Legend ) and a docudrama from 1971, Ballada o krasnom kapitane ( Ballad of the Red Captain ), as well as a radio program from 1968, Zhizn' i prikliucheniia krasnogo kapitana ( The Life and Adventures of the Red Captain ), in which he and his widow were lionized. It illustrates the ways by which the broadcasting media could serve to develop and maintain an essentially mythic image which supplanted the underlying reality, not only in the public mind but also in the private memory of the subject's close relatives.